212k views
3 votes
Py+7=6y+qp, y, plus, 7, equals, 6, y, plus, q y=y=y, equals

User Franchise
by
5.5k points

2 Answers

4 votes

Answer:

y= pāˆ’6 /qāˆ’7

ā€‹

Explanation:

The strategy

Move all y-terms on one side of the equation, and move all constant terms to the other side of the equation.

Using the distributive property, group like terms together on both sides of the equation.

To isolate y, divide both sides by the coefficient of y.

Solving for y

py+7 = 6y+q

py+7 -6y = q

py-6y= q - 7

y(p-6) = q-7

ā€‹

User Maikon
by
6.4k points
4 votes

Py +7 = 6y + qp

Solve the equation for y

To solve the equation for y we need to get y alone

Py +7 = 6y + qp

Subtract 6y from both sides

Py - 6y +7 = + qp

Subtract 7 from both sides

Py - 6y = + qp - 7

Now factor out y

(P - 6)y = qp - 7

Divide by P - 6 from both sides


y =(qp - 7)/((P - 6))

User Chuck Batson
by
6.3k points